A Wayfinding Mobile Application for Visually Impaired Users in Wellington Regional Hospital - Churcher, Harrison Blackburn (Wellington Faculty of Engineering Symposium, 2023)
Hospitals can be very difficult and confusing to navigate, and visitors can get lost easily, resulting in missed appointments. This not only causes inconvenience for patients and visitors, but also consumes valuable staff time as they assist in giving directions. This is especially an issue in the Wellington Regional Hospital where refurbishments and the addition of buildings have only made this more confusing. This problem is particularly acute for visually impaired people who may require additional assistance with wayfinding. This project aims to design and develop an existing wayfinding mobile application to enable interactive wayfinding for both visually-impaired and non-impaired users at the Wellington Regional Hospital. The existing application did not implement turn-by-turn navigation or accurate location detection. The project developed a new mapping service in the existing application, and further built on the application by including turn-by-turn navigation and audio prompts. Improved location detection are achieved by the use of Bluetooth Low Energy (BLE) beacons deployed around the wayfinding area. Evaluation of the mobile application involved visually-impaired and non-impaired individuals navigating to a location in order to determine the feasibility and overall success of the application. This analysis gathered invaluable insights, assessing not only the application's feasibility but also its accuracy, and overall effectiveness in addressing the complex wayfinding challenges faced by both categories of users.